Rigoletto [an opera in three acts] - Verdi, Giuseppe 1813-1901 (Opera Australia, 2011)
One of Opera Australia's best-loved productions, Elijah Moshinsky's retelling of Rigoletto draws Verdi's dark melodrama into a modern day mafioso underworld, inspired by Federico Fellini's all-time classic La Dolce Vita. Heading a glittering international cast is baritone Alan Opie in a commanding performance as the tortured jester, with Emma Mathews taking on the role of Gilda and Paul O'Neil as the lustful Duke. Conductor Giovanni Reggioli sympathetically captures the luscious yet fragile tones of Verdi's much-loved scrore, with it feast of sublime singing
Interpr. u.a.: Alan Opie [Rigoletto]. Emma Matthews [Gilda]. Paul O'Neill [Duke of Mantua]. David Parkin [Sparfucile]. Elizabeth Campbell [Giovanna]. Christopher Hillier [Count Ceprano]. Gennadi Dubinsky [Count Monterone]. Opera Australia Chorus. Michael Black [Choreinstud.]. Australian Opera and Ballet Ochestra. Giovanni Reggioli [Dir.]. Elijah Moshinsky [Bühnenregie]. Cameron Kirkpatrick [Filmregie]. - Live-Aufn.: Sydney, Opera House, 18. September 2010. - Ital. gesungen. - Text des Beih.: engl., franz., dt. - Untertitel: engl., franz., dt., span., ital. - Enth. Bonusmaterial: Cast gallery
Keywords: Verdi, Giuseppe -- 1813-1901 -- Rigoletto; Stölzl, Philipp -- 1967-; Bregenzer Festspiele -- 2020 -- Bregenz; Geschichte 2019; Inszenierung; Film; DVD-Video